Phenotypic detection and molecular characterization of beta-lactamase genes among Citrobacter species in a tertiary care hospital - Ashok Kumar Praharaj (Thieme Medical and Scientific Publishers Pvt. Ltd., 2016)
Objective: To examine the distribution, emergence, and spread of genes encoding beta-lactamase resistance in Citrobacter species isolated from hospitalized patients in a tertiary care hospital. Methods: A prospective study was conducted in a 1000-bed tertiary care center in Pune, India from October 2010 to October 2013. A total of 221 Citrobacter spp. isolates were recovered from clinical specimens from different patients (one isolate per patient) admitted to the surgical ward, medical ward and medical and surgical Intensive Care Units. Polymerase chain reaction (PCR) assays and sequencing were used to determine the presence of beta-lactamase encoding genes. Conjugation experiments were performed to determine their transferability. Isolate relatedness were determined by repetitive element based-PCR, enterobacterial repetitive intergenic consensus-PCR and randomly amplified polymorphic DNA. Results: Among 221 tested isolates of Citrobacter spp. recovered from various clinical specimens, 179 (80.9%) isolates showed minimum inhibitory concentration (MIC) >4 μg/ml against meropenem and imipenem. One hundred and forty-five isolates with increased MICs value against carbapenems were further processed for molecular characterization of beta-lactamase genes. Susceptibility profiling of the isolates indicated that 100% retained susceptibility to colistin. Conjugation experiments indicated that blaNDM-1was transferable via a plasmid. Conclusion: The ease of NDM-1 plasmid transmissibility may help their dissemination among the Citrobacter species as well as to others in Enterobacteriaceae. Early detection, antimicrobial stewardship and adequate infection control measures will help in limiting the spread of these organisms.